An Analysis of the Students' Ability to Translate Short Text - Nurhalimah Nurhalimah (EXCELLENCE: Journal of English and English Education, 2025)
This study examines how well fourth- and sixth-semester students at UPMI Medan can translate short stories as part of their assignment in the Indonesian-English Interpretation subject study. The translation used five methods: Borrowing, Literal Translation, Transcription, Modulation, and Adaptation. The text analysis was based on the acceptability rating instrument and readability rating instrument theories. To determine the final score, the translation assessment guidelines by Machali (2000: 119-120) were used. The results show that the students' translation skills are at a moderate level, with their ability, their direct translations are acceptable, and the overall quality of their translation is also acceptable. The benefit of this study is to determine the extent of students' abilities in translating texts, so that they can be followed up and directed to areas where they are lacking in translation